Nanographene Metallaprisms: Structure, Stimulated Transformation, and Emission Enhancement. Issue 38 (17th August 2022) - Chai, Ling; Ju, Yang‐Yang; Xing, Jiang‐Feng; Ma, Xiao‐Hui; Zhao, Xin‐Jing; Tan, Yuan‐Zhi
Abstract: Nanographenes are inclined to assemble into stacked columnar structures that are stabilized by π‐π interactions, whereas other supramolecular structures of nanographenes, such as prisms and cages, are rarely investigated. Herein, a diazananographene was synthesized, and then assembled with a coordination unit, thereby producing a triangular metallaprism. After adding C60 or C70, the triangular metallaprism was transformed into a square tetramer, which encapsulated a pair of C60 or C70 molecules. The formed host‐guest complex demonstrated efficient energy transfer from the diazananographene shell to the C60 cores. The emission intensity of the capsulated C60 was enhanced remarkably, compared with free C60, due to an increased quantum yield and optical absorption coefficient. This work demonstrates the versatility of nanographene‐based supramolecular architectures beyond columnar stacking and their ability to enhance the emission of otherwise non‐emissive fullerene. Abstract : A triangular metalloprism was constructed by supramolecular assembly of diazananographene and was transformed into a square tetramer by stimulation with C60 /C70 . A pair of C60 /C70 molecules can be encapsulated in the square tetramer. A remarkable emission enhancement of the trapped C60 was observed, which was attributed to the formation of a confined dimer and efficient intermolecular energy transfer.